Outcome of Desarda Technique in Inguinal Hernia Repair - Jehanzaib Rashid, Rana Shoaib Aslam, Muhammad Hassan, Assam Arshid, Muhammad Farooq Afzal, Awais Amjad Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study is to evaluate the short term outcome of Desarda technique in inguinal herniorrhaphy in terms of duration of surgery and post-operative pain. Material and methods: This case series study was conducted at Department of Surgery, Lahore General Hospital, Lahore from June 2021 to December 2021. Total 150 male patients of inguinal hernia having age 16-50 years were selected. Duration of surgery and post-operative pain was studied. Results: The mean age of patients was 34.86 ± 9.38 years with range of 31.00 years. The minimum and maximum age was 19.00 and 50.00 years respectively. The mean surgery time was 48.92 ± 11.13 minutes with minimum and maximum of 30 and 70 minutes. There were 11 (7.33%) patients who had no pain, 32 (21.33%) had mild, 91 (60.67%) had moderate and 16 (10.67%) had severe pain at day 1. At day 2, no pain was found in 53 (35.33%) patients. A majority of patients 73 (48.67%) were suffering from mild pain whereas moderate and severe pain was seen in 22 (14.67%) and 2 (1.33%) patients respectively. Conclusion: Desarda repair is an acceptable alternative technique for effective repair of inguinal hernia with comparable operative time and postoperative pain as observed in this study that there is minimal duration of surgery and less post operative pain especially at day 2 . The technique can be safely employed to reduce the hospital burden and morbidity related to post-operative pain following operative repair of inguinal hernia. The study will help to encourage further research on this technique as there is only sparse data available in the published local literature to date. Keywords: Inguinal hernia, Herniorrhaphy, Desarda, duration of surgery, postoperative pain.